The ABC's of choosing a good wife - Wood, Stephen (Port Charlotte, FL : Family Life Center Publications, 2003)
"How to find & marry a great girl"--Cover.
Includes bibliographical references (p. 167-168).
Keywords: Mate selection; Mate selection -- Religious aspects -- Christianity; Courtship -- Religious aspects -- Christianity; Dating (Social customs) -- Religious aspects -- Christianity; Love -- Religious aspects -- Christianity; Marriage -- Religious aspects -- Christianity; Single men -- Conduct of life; Single men -- Religious life; Single people -- Conduct of life; Single people -- Religious life